IMPROVEMENT OF THE MECHANISM FOR REGULATING EVALUATION ACTIVITIES BASED ON WORLD EXPERIENCE - Khomitov K. Z.; Kholboev I. U. (American Journals, 2025)
This article provides recommendations for improving the mechanism for regulating appraisal activities based on models of world experience and their application in the practice of Uzbekistan. The experience of models of such countries as the USA, the Russian Federation and Germany in regulating appraisal activities, their maximum proximity to the requirements of the property appraisal services market, and in particular their contribution to stabilizing the value of property are also described. And this is just right for regulating the property appraisal services market in Uzbekistan.
Keywords: Property, cost, assessment, price, assessment activity, regulation, coordination, control, model, real estate market, property assessment services market.